The Oxford handbook of China innovation - Fu, Xiaolan, 1967-; Chen, Jin, 1968-; McKern, Bruce (New York : Oxford University Press, 2021)
This handbook provides an authoritative in-depth understanding of China's progression and future global position from over sixty leading scholars on China, who explain the development of China's innovation capabilities, the causes and their views about the future direction. Xiaolan Fu, Jin Chen, and Bruce McKern bring together international scholars and experts to explain how China managed, in a very short period of time, to become the world's second-largest economy and a leader in many fields of innovation.
Introduction: China's Journey to Innovation / Xiaolan Fu, Bruce McKern, Jin Chen, Ximing Yin -- Entrepreneurship and Innovation of Small and Medium-Sized Enterprises in China / Jin Chen, Liying Wang -- Financing for innovation in China / Jin Chen, Liying Wang -- Innovation and Entrepreneurship Education and Its Implications for Human Capital Development in China / Fang Lee Cooke -- System Reform, Competition, and Innovation in China / Weiying Zhang -- Reforms of the Science and Technology Management System / Zhijian Hu, Zhe Li, Xianlan Lin -- Mass entrepreneurship and Mass Innovation in China / Jian Gao, Rui Mu -- The Role of Clusters in the Development of Innovation Capabilities in China / Tuoyu Li, Jiang Wei -- China's Science-Based Innovation and Technology Transfer in the Global Context / Jizhen Li, Ximing Yin, Subrina Shen -- Science Parks and High-tech Zones / Susan M. Walcott -- Venture Capital, Angel Capital and Other Finance, IPOs and Acquisitions / Lin Lin -- Capabilities Accumulation and Development: What History Tells the Theory / Giovanni Dosi, Xiaodan Yu -- Intellectual Property Rights Protection / Can Huang, Naubahar Sharif -- Innovation Elements in Traditional Chinese Culture / Jin Chen, Qingqian Wu -- Innovation Strategies of MNCs in China and their Contribution to the National Ecosystem / Bruce McKern, George S. Yip, Dominique Jolly -- China's International Migration: Status and Characteristics / Huiyao Wang -- Chinese Outward Foreign Direct Investments and Innovation / Vito Amendolagine, Xiaolan Fu, Roberta Rabellotti -- Internationalisation of Chinese Research and Development / Max von Zedtwitz, Xiaohong Iris Quan -- International Innovation Collaboration in China / Kaihua Chen, Ze Feng, Xiaolan Fu -- Open Innovation for Development in China / Jin Chen, Yufen Chen -- Chinese Cost Innovation, the Shanzhai Phenomenon and Accelerated Innovation / Peter J. Williamson
Also issued in print: 2021.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on November 10, 2021).
Keywords: Economic development -- China; Technological innovations -- Economic aspects -- China; International business enterprises -- Technological innovations -- China; Information technology -- China -- Management; Organizational change -- China; China -- Economic policy -- 21st century